Poverty and vulnerability in Mexico: The case of young people who do not study nor work - Aguila, Emma; Mejía, Nelly; Pérez, Francisco; Rivera, Alfonso; Ramírez, Edgar (Estudios Económicos de El Colegio de México, 2015)
Recently, the phenomenon of young people not in education, employment or training (NEET) has come to the fore due to the risks associated to this situation. The contribution of this paper is in its analysis of this population’s composition, dynamics, poverty patterns, individual and family characteristics, as well as projections for 2030. In addition, we propose a classification for NEET’s that could be used for the design of public policies and that was used to identify that this population will tend to decreased due to the proportion of women who study and join the labor force and that, in the future, the unemployed will out number other groups.